ELECTRONIC VOTING IN INDONESIA: HEAD OF VILLAGE ELECTION - Ramadhan, Adityo Pratikno; Fitriani, Anita Pebri; Suharto, Sugeng; Hendrastiti, Titiek Kartika (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2018)
What if electronic voting performs in a rural area that has a limited condition of infrastructure and people who are peculiar with technology such as a computer? This article answers this question. Elections in Indonesia at national, province and district level are still used ballot paper. However, there is a village in Indonesia that use remote electronic voting system as a tool to vote head of the village. This research used the interview as a primary data collection and this research interviewed 17 key informants that directly involved in the village electronic voting. The research found the village voters more convenient in an electronic voting than the ballot paper system and the electronic voting can perform in a place that the people not familiar with modern technology. The unique finding of this research is the cost for electronic village election came from the village head candidates that shared the total cost of electronic voting. The other findings are electronic voting can be performed in an area with limited infrastructures and community that peculiar with technology.hence, it is possible for Indonesia to implement electronic voting in a level that higher than village voting, such as regent or mayor election.